Features of the functioning of the institute of military chaplains in Ukraine: national problems and projection into international experience - Лук’янова, Галина; Бекерська, Тетяна; Lukianova, Halyna; Bekerska, Tetiana (Видавництво Львівської політехніки, 2025)
У статті опрацьовано передумови становлення та реалізації служби інституту військових капеланів, її важливість та актуальність в умовах понаддесятирічної війни та повномасштабного незаконного воєнного вторгнення на територію незалежної України. Знання про роль і місце військових капеланів у збройних силах, особливості їх душпастирської діяльності потрібні насам- перед для повноцінного функціонування Українських Збройних сил, до складу яких входять люди, що зберігають своє психологічне здоров’я та стійкість, будучи максимально наближеними до християнської віри та релігії. Важливим є дослідження системи організації військового капеланства у військових форму- ваннях України та ЗСУ з урахуванням історичного досвіду, традиційних вірувань і культури українського народу. Капеланство ‒ термін, що походить від слова “капелан” і означає службу капелана, інститут духівників у суспільстві. До їхніх функцій належить богослужіння серед військовослужбовців, контроль за їхнім моральним станом, відспівування померлих (загиблих) тощо. Особливу увагу присвячено взаємозв’язку між процесом демократизації суспільства та становленням інституту військового капеланства в Україні. Саме демократичні перетворення, що супроводжували здобуття незалежності, стали рушійною силою змін у державно-церковних відносинах. Перехід до нової політичної системи потребував переосмислення ролі релігії в су- спільстві, що сприяло відродженню інституту військового духовенства, який раніше зазнавав ігнорування або фальсифікації. В Україні недостатньо розвинута концепція використання капеланів у контексті націо- нальної безпеки та оборони, що обмежує їхнє стратегічне значення. Роль капеланства могла б бути більш чітко визначена в межах національної стратегії для забезпечення духовної і моральної стійкості нації, особливо в умовах війни. Військові священники (капелани) є у більшій частині армій світу (у США і Франції, існує інститут військового священства, що перебуває на державному забезпеченні). На рівні актів національного законодавства їхня присутність заборонена лише в арміях Китаю і Північної Кореї. Така ситуація є цілком зрозумілою та відповідає різноманітності релігійних ідеологій різних людей, оскільки навіть якщо дивитися на це винятково з прагматичних позицій, релігія є чинником державної безпеки. Релігія забезпечує психологічний комфорт у суспільстві, прищеплює громадянам високі моральні ідеали і, зрештою, визначає характер економічного та політичного розвитку держави.Вважаємо, що важливою є участь з 1 по 7 лютого 2025 року України у Всесвітньому Тижні міжрелігійної гармонії World Interfaith Harmony Week. Ця глобальна ініціатива була започат- кована з метою сприяння гармонії та взаєморозумінню між різними релігіями світу. У війську України є дефіцит військових капеланів. Є багато євангельських служителів, які прагнуть стати військовими капеланами, але не відповідають цензовим вимогам за законодавством України. Одна з причин полягає в тому, що кількість тих, хто бажає отримати капеланські посади у ЗСУ, значно перевищує кількість мандатів, що є доступними для євангельських служителів за державною квотою, оскільки розподіл квот конфесійного представництва військових капеланів здійснюється з урахуванням конфесійної належності особового складу відповідно Збройних сил України. Інститут військового капелана сьогодні є невід’ємною частиною українського війська, тим паче в умовах дії правового режиму воєнного стану. Місія капелана не полягає у конфесійності. Капелан – це універсальний офіцер, який робить загальні функції, які стосуються кожного солдата, навіть атеїста. Він допомагає солдатові служити, виконувати бойові і небойові завдання.

The article deals with the prerequisites for the formation and implementation of the service of the institute of military chaplains, its importance and relevance in the context of more than a decade of war and a full-scale illegal military invasion of the territory of independent Ukraine. Knowledge of the role and place of military chaplains in the armed forces, the peculiarities of their pastoral activities is necessary primarily for the full functioning of the Ukrainian Armed Forces, which include people who maintain their psychological health and resilience by being as close as possible to the Christian faith and religion. It is important to study the system of organization of military chaplaincy in the military formations of Ukraine and the Armed Forces of Ukraine, taking into account the historical experience, traditional beliefs and culture of the Ukrainian people. Chaplaincy is a term that comes from the word “chaplain” and means the service of a chaplain, the institution of clergy in society. Their functions include worship among military personnel, control over their moral condition, funeral services for the dead (deceased), etc. Particular attention is paid to the relationship between the process of democratization of society and the formation of the institute of military chaplaincy in Ukraine. It was the democratic transformations that accompanied the achievement of independence that became the driving force behind changes in church-state relations. The transition to a new political system required a rethinking of the role of religion in society, which, in turn, contributed to the revival of the institution of military clergy, which had previously been ignored or falsified. In Ukraine, the concept of using chaplains in the context of national security and defense is underdeveloped, which limits their strategic importance. The role of chaplaincy could bemore clearly defined within the national strategy to ensure the spiritual and moral stability of the nation, especially in times of war. Most armies in the world have military priests (chaplains) (in the United States and France, there is an institution of military priesthood that is state-supported). At the level of national legislation, their presence is prohibited only in the armies of China and North Korea. This situation is quite understandable and corresponds to the diversity of religious ideologies of different people, because even if we look at it from a purely pragmatic point of view, religion is a factor of state security. Religion provides psychological comfort in society, instills high moral ideals in citizens, and ultimately determines the nature of the economic and political development of the state. We believe that it is important that Ukraine takes part in the World Interfaith Harmony Week from February 1 to 7, 2025. This global initiative was launched to promote harmony and mutual understanding between different religions of the world. There is a shortage of military chaplains in the Ukrainian army. There are many evangelical ministers who aspire to become military chaplains, but do not meet the qualification requirements under Ukrainian law. One of the reasons is that the number of those wishing to obtain chaplaincy positions in the Armed Forces far exceeds the number of mandates available to evangelical ministers under the state quota, since the distribution of quotas for the denominational representation of military chaplains is based on the denominational affiliation of the personnel of the Armed Forces of Ukraine. The institute of military chaplain is an integral part of the Ukrainian army today, especially under the legal regime of martial law. The mission of a chaplain is not confessional.A chaplain is a universal officer who performs general functions that concern every soldier, even an atheist. He helps the soldier to serve. He helps the soldier to perform combat and non-combat tasks.
Особливості функціонування інституту військових капеланів в Україні: проблеми національного масштабу та проєкція у міжнародний досвід
Keywords: інститут військових капеланів; воєнний стан; душпастирська діяльність; Збройні сили України; капелан; капеланство; військовослужбовці; церква; богослужіння; релігія; законодавство; правові проблеми; удосконалення законодавства; військова служба; правовий ре- жим; релігійні обряди; армія; церква; психологічна підтримка; фінансування; держава; конфесія; institute of military chaplains; martial law; pastoral activity; Armed Forces of Ukraine; chaplain; chaplaincy; military personnel; church; worship; religion; legislation; legal problems; improvement of legislation; military service; legal regime; religious rites; army; church; psychological support; financing; state; denomination; 35.071.2; 355.02(477)